Ist soziale Gerechtigkeit eine Illusion? - Barry, Brian (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
The article discusses the implications of the conception of social justice in Hayek's writings. To approach distributional justice by means of moral theory is a hopeless undertaking in Hayek's eyes, because market processes generating distribution in modern societies function in an abstract way. Therefore, these processes are immune to moral assessments. In a detailed critique of this thesis, the author tries to show that moral criteria can indeed be applied to market processes.